Hippocampal sclerosis, TDP‐43, and the duration of the symptoms of dementia of AD patients. Issue 9 (31st July 2020) - Lopez, Oscar L.; Kofler, Julia; Chang, YueFang; Berman, Sarah B.; Becker, James T.; Sweet, Robert A.; Nadkarni, Neelesh; Patira, Riddhi; Kamboh, M. Ilyas; Cohen, Ann D.; Snitz, Beth E.; Kuller, Lewis H.; et al.
Abstract: Objectives: To examine the relationship between duration of the cognitive symptoms, from the earliest reported symptom to death, and hippocampal sclerosis (HS) and TAR‐DNA binding protein of 43kDA (TDP‐43) in Alzheimer's disease (AD) patients. Methods: The study was conducted in 359 cognitively impaired patients who met the pathological criteria for AD (NIA‐Reagan intermediate or high). The mean age at onset was 69.5 ± 8.8 years (range 37‐95) and the mean duration of the symptoms was 10.5 ± 4.2 years. The association between symptoms duration and HS and TDP‐43 was examined with logistic regression analyses controlling for age at death, atherosclerosis in the Circle of Willis (CW), cerebral infarcts, gender, baseline Mini Mental State Examination scores, APOE‐4 allele, and presence of Lewy bodies (LB). Results: HS was present in 18% (n = 64) and TDP‐43 in 51.5% (n = 185) of the patients. HS and TDP‐43 were more frequent in patients whose symptoms lasted more than 10 years. LBs were present in 72% of the patients with HS and in 64% of the patients with TDP‐43. Age at onset was not associated with TDP‐43 or HS. HS was associated with duration of symptoms and LB, TDP‐43, and atherosclerosis in the CW. TDP‐43 was associated with duration of symptoms, LB, and HS. Interpretation: HS and TDP‐43 are present in early and late onset AD. However, their presence is mainly driven by the duration of symptoms and the presence of LB. This suggests that HS and TDP‐43 are part of the later neuropathological changes in AD.